O-30 Micro-EMG: Imaging human motor units using a novel intramuscular electrode array. Issue 7 (July 2019) - Maitland, Stuart; Escobedo-Cousin, Enrique; Schofield, Ian; O'Neill, Anthony; Baker, Stuart; Whittaker, Roger
Abstract : Background: State of the art clinical EMG provides only indirect or inferred measurements of muscle structure. Structural information for motor units has only previously been described using laborious glycogen depletion experiments. Micro-EMG is a novel multi-electrode system that samples EMG signal from 64 electrodes along the surface of the needle in order to localise the muscle fibres of multiple human motor units along the length of a clinical EMG needle. This enables mapping of human motor units from just 5 min recordings. Methods: We recorded multi-electrode EMG activity at varying force levels (10–40% of maximum voluntary contraction) in the biceps and tibialis anterior muscle of 6 healthy volunteers. Each EMG channel was decomposed into motor unit action potentials, and fibre action potentials spatially localised using a signal deconvolution method. Features normally only accessible via histology including fibre nearest neighbour distance and all-pairs distance were calculated. Several simulations of muscle electrical activity were created in order to test the accuracy of localisation. Results: For the first time, we were able to produce an electrical localisation map of the human motor unit in vivo. A total of 340 fibres in 31 motor units were isolated and localised. Median nearest neighbour distance varied from 0.44 to 1.02 mm. Simulation findings indicated strong accuracy in fibre number estimation and localisation. Conclusions: Micro-EMG provides unprecedented insights into motor unit structure and function. We anticipate that this method will provide useful biomarkers for disease states such as motor neurone disease.